Effects of intercropping with post-grafting generation of Cosmos sulphureus on physiological and growth of grape seedling under cadmium stress. Issue 2 (April 2020) - Wang, Xun; Xu, Xiangting; Xiao, Yunying; Wei, Xiaohan; Wang, Yan; Liao, Ming'an
Abstract: A pot experiment was conducted to study the effects of intercropping with post-grafting generation of Cosmos sulphureus on physiological growth of grape seedlings under cadmium stress by determining the biomass, the chlorophyll a, chlorophyll b, total chlorophyll and carotenoid content, the activities of superoxide dismutase (SOD) and catalase (CAT) and the soluble protein and sugar content. All in all, these results illustrated that intercropping with post-grafting generation of C. sulphureus increased the biomass, photosynthetic pigment and osmotic substance content and also enhance the antioxidant enzyme activities compared to the grape seedlings monoculture, especially intercropping with post-grafting generation of C. sulphureus of self-rooted grafting by two different development stages of plant seedling. Thus, intercropping with post-grafting generation of C. sulphureus played an important role in grape seedlings restoration even under cadmium stress and also provided theoretical basis for other plant restoration.